Knowledge of Emerging and Reemerging Infectious Diseases in the Public of Guangzhou, Southern China - Ma, Xiaowei; Lu, Jianyun; Liu, Weisi (Frontiers in Public Health, 2022)
Objective: To get the overall picture about the knowledge of emerging and re-emerging infectious diseases in public in Guangzhou and provide a scientific basis for developing health information strategies. Methods: We used the structured questionnaire to interview 1,000 Guangzhou residents by health enquiry hotline. Descriptive analysis was presented to evaluate knowledge of the participants. Multiple logistic regression model was performed to determine the influence factors for knowledge of emerging and re-emerging infectious diseases Results: 801 individuals completed the survey. About one third had heard of Middle East respiratory syndrome and Zika, while Ebola and plague about 50%. 32.08% participants had never heard of any of the four diseases. Only 2.08% knew the sexual transmission of Zika and 90.17% had no idea about the epidemic region of plague. No more than 15% knew they should check their health status after returning from the epidemic region. Education level and income were the key factors that influenced knowledge rate. Conclusions: The low-level knowledge called for the improvement of health information to the public, especially those with low level of education and income. Effective and precise health information was urged to carry out to improve the prevention for the emerging and re-emerging infectious diseases.